(untitled) (Journal of Comparative & International Higher Education, 2024)
This paper offers a comparative analysis of internationalization policy between two distinct nations entrenched in unique sociopolitical and economic cultures, namely Japan and the United States of America (U.S.A.). How do different policy-making processes impact internationalization policy in practice? While Japan’s internationalization policy is clearly articulated at the national level, the U.S. does not have a national higher education internationalization policy that emanates from the federal government. Therefore, in this study we analyzed macro-level data from three distinct policy-making sectors to identify U.S. national policy. Our analysis identifies the policy-making process in each nation and elucidates how internationalization policy unfolded in both cases. Second, we compare the development of higher education internationalization policy efforts in the two countries, sequencing events, factors, and rationales that impacted national policy. This approach allowed us to compare the implications of having a centralized versus a pluralistic internationalization policy-making process in the 2000s. Our research shows that, in practical terms, there is more variation in higher education internationalization policy in the U.S. than in Japan. In both countries, policy dynamics were influenced by social and economic factors, and political factors influenced policy in the U.S. An academic and humanitarian rationale for internationalization policy was not central to the essence of the policy in either country.